2004
DOI: 10.1016/j.cub.2004.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Actin Filaments Align into Hollow Comets for Rapid VASP-Mediated Propulsion

Abstract: For cells, the growth of a dense array of branched actin filaments organized by the actin-related proteins 2 and 3 (Arp2/3) complex at the plasma membrane offers an explanation as to how movement is produced, and this arrangement is considered to be optimal for motility. Here, we challenged this assumption by using an in vitro system of polystyrene beads in cell extracts that contained a complex mix of actin polymerization proteins as in vivo. We employed the surface of the bead as a reactor where we mixed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 23 publications
(10 reference statements)
7
40
0
1
Order By: Relevance
“…Our observations on the de novo generated networks on permeabilised cells indeed shows that the mere re-creation of a localized Arp2/3 network at the edge of the cell is not sufficient to promote a protrusion, suggesting that the presence of the membrane might indeed be essential to restrict polymerization within a 2D plane and preserve preferred lamellipod thickness. Altogether, this data concurs with recent evidence suggesting that, although the Arp2/3 complex is an important factor in determining the morphology of actin-based cellular structures [Svitkina and Borisy, 1999;Vignjevic et al, 2003], proper geometry of the actin cytoskeleton in cells is essential for lamellipod protrusion and cell motility [Bear et al, 2002;Vignjevic et al, 2003;Mejillano et al, 2004;Plastino et al, 2004;Atilgan et al, 2005].…”
Section: Discussionsupporting
confidence: 91%
“…Our observations on the de novo generated networks on permeabilised cells indeed shows that the mere re-creation of a localized Arp2/3 network at the edge of the cell is not sufficient to promote a protrusion, suggesting that the presence of the membrane might indeed be essential to restrict polymerization within a 2D plane and preserve preferred lamellipod thickness. Altogether, this data concurs with recent evidence suggesting that, although the Arp2/3 complex is an important factor in determining the morphology of actin-based cellular structures [Svitkina and Borisy, 1999;Vignjevic et al, 2003], proper geometry of the actin cytoskeleton in cells is essential for lamellipod protrusion and cell motility [Bear et al, 2002;Vignjevic et al, 2003;Mejillano et al, 2004;Plastino et al, 2004;Atilgan et al, 2005].…”
Section: Discussionsupporting
confidence: 91%
“…Anti-capping factors such as Ena/VASP proteins would therefore be predicted to decrease branching by the reduction of barbed-end capping, which would lead to the increased consumption of monomers through their addition to barbed ends. It has also been proposed that Ena/VASP exerts a catalytic debranching effect on Arp2/3 branches (Plastino et al, 2004;Samarin et al, 2003); however, this idea needs to be confirmed with more direct assays such as TIRF. Future experiments will be required to delineate the precise role of Ena/VASP in Arp2/3 branch dynamics.…”
Section: Anti-branchingmentioning
confidence: 99%
“…Several groups have noted that Ena/VASP proteins reduce the frequency of actin-filament branching by the Arp2/3 complex (Bear et al, 2002;Plastino et al, 2004;Samarin et al, 2003;Skoble et al, 2001). The strongest evidence for a direct antibranching effect comes from the work of Skoble and colleagues (Skoble et al, 2001).…”
Section: Anti-branchingmentioning
confidence: 99%
“…Subsequently the WASP proteins and the related Scar/WAVE molecules were picked apart by absorbing different protein fragments to bead surfaces and observing which domains gave optimal actin network growth and optimal motility in cell extracts and pure protein mixes [46][47][48]. Different domains from different actin-binding proteins were also absorbed simultaneously and in different proportions to bead surfaces, for example to recruit and activate the Arp2/3 complex in varying proportions with Ena/VASP proteins [49]. When formin proteins were identified as actin polymerization nucleators that produced unbranched networks, in contrast to the Arp2/3 complex-based branched networks, formin-based actin assembly and movement were also reproduced on bead surfaces [50,51].…”
Section: What To Coat the Beads With?mentioning
confidence: 99%